A readaptação do rádio a partir da internet : uma análise dos modelos da BBC e da Rádio Gaúcha - Gamba, Filipe Pereira (2018)
This dissertation deals with the imbricated relationship between radio and the internet, given that technological evolution has modified the forms of communication and in this new conjecture different possibilities for the radio are extended. It starts from the premise that the current moment strengthens the media convergence and implies transformations ─ not only in the concept of radio, but also in the way of making radio and in the way the content happens to be consumed. It is pointed out that this work aims to research the radio adaptation from the internet. In this scope two important transformations will occur that have occurred in different proposals: on the radios of the British Broadcasting Corporation (BBC) from the United Kingdom and Radio Gaucha from Porto Alegre. As for BBC its strategies based on the segmentation of radio content - the so-called radio on demand were mapped. In contrast Rádio Gaúcha anchors its changes in social networks. It should be noted that the model adopted by the BBC serves as a reference for a readaptation in which the radio preserves its essence: audio; in contrast, Rádio Gaúcha bases its propagation on social platforms, through the adoption of languages that go beyond audio. These are different readaptations in the form of making radio, from the internet, which exemplify the imperious adaptations of the vehicle in face of the transformations that have occurred in the last decades.